1999
DOI: 10.1002/(sici)1097-0134(19990101)34:1<29::aid-prot4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

New general approach for determining the solution structure of a ligand bound weakly to a receptor: structure of a fibrinogen A?-like peptide bound to thrombin(S195A) obtained using NOE distance constraints and an ECEPP/3 flexible docking program

Abstract: A new approach incorporating flexible docking simulations and NMR data is presented for calculating the bound conformation of a ligand that interacts weakly with an enzyme. This approach consists of sampling directly the conformation of a flexible ligand inside a receptor active site containing surrounding flexible loops. To make this sampling efficient, a ligand-growing procedure has been adopted. Optimization of the ECEPP/3-plus-NOE constraint function is carried out by using a collective variable Monte Carl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 75 publications
(171 reference statements)
2
18
0
Order By: Relevance
“…A harmonic force was imposed when the distance violation was more than the user-defined minimal distance, i.e., 5 Å for the first minimization steps and 3 Å for the following two minimization steps. If the violation was more than 2 Å from the minimal distance, the harmonic distance was replaced by a quasi-linear branch (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A harmonic force was imposed when the distance violation was more than the user-defined minimal distance, i.e., 5 Å for the first minimization steps and 3 Å for the following two minimization steps. If the violation was more than 2 Å from the minimal distance, the harmonic distance was replaced by a quasi-linear branch (29).…”
Section: Methodsmentioning
confidence: 99%
“…Mutational studies have revealed the mutual binding sites on IFN-␣2 and ifnar2. On IFN-␣2, ifnar2 binds to the A helix (residues 12-15), the AB loop (residues [26][27][28][29][30][31][32][33][34][35], and the E helix (residues 144-153) (7), whereas on ifnar2, IFN-␣2 binds to three loops of the N-terminal domain of the receptor (residues 45-52, 75-82, and 102-106) with no significant binding detected toward the Cterminal domain (8)(9)(10). Determination of the receptor-ligand structure will significantly promote our understanding of IFN signaling at the molecular level.…”
mentioning
confidence: 99%
“…Limiting the conformational space using knowledge-based constraints is often crucial for successful peptide docking. The constraints may come from experiments (such as NOE data 80 ) or from previous knowledge of conserved positions for some of the peptide residues. [81][82][83] Scheraga and coworkers used a ''ligand-growing'' procedure.…”
Section: Structure-based Approaches For Peptide Design and Optimizationmentioning
confidence: 99%
“…It was applied to determine the structure of a fibrinogen A alike peptide bound to an active-site mutant of thrombin. 80 Schafroth and Floudas defined the pockets binding each of the peptide residues based on the known structure of the complex of a major histocompatibility complex (MHC) molecule HLA-DRB1*0101 with a cognate peptide, and used deterministic global optimization to dock MHC peptides. The pockets were predefined and considered to be independent of each other and the protein was considered to be rigid.…”
Section: Structure-based Approaches For Peptide Design and Optimizationmentioning
confidence: 99%
“…One approach to molecular docking is through descriptors of the surface shape5, 6 with provision for a limited degree of flexibility 4, 7, 8. A number of groups2, 3, 9–18 have utilized all‐atom models based on a molecular mechanics force field, with sampling of conformations by molecular mechanics, Monte Carlo, genetic algorithms, or distance embedding. More recent docking studies strive to include flexibility of the ligand and/or receptor.…”
Section: Introductionmentioning
confidence: 99%